Responsive 3D printed microstructures based on collagen folding and unfolding - Mainik, Philipp; Aponte-Santamaria, Camilo; Fladung, Magdalena; Curticean, Ernest Ronald; Wacker, Irene; Hofhaus, Götz; Bastmeyer, Martin; Schröder, Rasmus R.; Gräter, Frauke; Blasco, Eva (Small, 2025)
Mimicking extracellular matrices holds great potential for tissue engineering in biological and biomedical applications. A key compound for the mechanical stability of these matrices is collagen, which also plays an important role in many intra- and intercellular processes. Two-photon 3D laser printing offers structuring of these matrices with subcellular resolution. So far, efforts on 3D microprinting of collagen have been limited to simple geometries and customized set-ups. Herein, an easily accessible approach is presented using a collagen type I methacrylamide (ColMA) ink system which can be stored at room temperature and be precisely printed using a commercial two-photon 3D laser printer. The formulation and printing parameters are carefully optimized enabling the manufacturing of defined 3D microstructures. Furthermore, these printed microstructures show a fully reversible response upon heating and cooling in multiple cycles, indicating successful collagen folding and unfolding. This experimental observation has been supported by molecular dynamics simulations. Thus, the study opens new perspectives for designing new responsive biomaterials for 4D (micro)printing.
Gesehen am 23.06.2025
Veröffentlicht: 27 November 2024